The war in Sri Lanka : unending conflict? - Mukarji, Apratim (New Delhi : Har-Anand Publications, 2000)
Analytical study of the seventeen-year old civil war and the Indo-Sri Lanka relations during the period; account by a journalist.
Includes index
Keywords: Tamil (Indic people) -- Sri Lanka -- Politics and government; Sri Lanka -- Politics and government -- 1978-; Sri Lanka -- Ethnic relations; Sri Lanka -- Foreign relations -- India; Sri Lanka -- History -- Civil War, 1983-2009.; India -- Foreign relations -- Sri Lanka